The role of communicative competence in marketing - Stahursky, Valery; Tkachuk (Stakhurska), Svitlana (My University, 2016)
The paper studies the role and significance of communication skills of staff in interactive marketing and also the importance of professional competence in classical marketing communications forming.
Keywords: комунікативна компетентність; комунікативні здібності персоналу; маркетингові комунікації; коммуникативная компетентность; коммуникативные способности персоналу; маркетинговые коммуникации; communicative competence; communication skills of staff; marketing communications; кафедра маркетингу